Transvaginal ultrasound ovarian diathermy: sheep as an experimental model - Pimentel Anita M; Kobayashi Danielle; Kliemann Lucia M; Franjdlich Renato; Capp Edison; Corleta Helena VE (BMC, 2012)
Abstract Background Some techniques of transvaginal ovarian drilling have been previously described. Nevertheless a monopolar transvaginal ovarian cauterization, that use the expertise and safety of transvaginal puncture for oocyte captation seems to be an easier and feasible approach. The aim of this study was to develop a minimally invasive ovarian cauterization technique under transvaginal ultrasound control, and to evaluate the safety of the transvaginal ovarian monopolar cauterization, female sheep at reproductive age were used as an experimental model. Findings An experimental study was performed in a university research center. Seventeen female sheep (15 Corriedale e 2 Suffolk) in reproductive age were submitted to transvaginal ovarian cauterization with a monopolar Valleylab Force 2 electrocautery. Macroscopic and microscopic lesions were assessed. Ovarian size were 1.31 cm2 ± 0,43 (Corriedale) and 3.41 cm2 ± 0,64 (Suffolk). From 30 ovaries from Corriedale sheep punctured, only 3 were cauterized, presenting macroscopic and typical microscopic lesion. In the Suffolk sheep group, only one ovary was cauterized. No lesion could be found in the needle path. Conclusions This is the first experimental animal model described for ovarian cauterization needle guided by transvaginal ultrasound. The sheep does not seem to be the ideal animal model to study this technique. Another animal model, whose ovaries are better identified by transvaginal ultrasound should be sought for this technique, theoretically less invasive, before it could be offered safely to women with polycystic ovary syndrome.